Analisis Implementasi Kebijakan Penurunan Stunting di Desa Penfui Timur Kabupaten Kupang - Deasi N. Paji; Masrida Sinaga; Galuh Wiedani K.D. Larasati (Pusat Riset dan Inovasi Nasional, 2025)
According to the anthropometric standards for evaluating children's nutritional status, stunting is a growth failure condition based on the weight-for-age (W/A) or height-for-age (H/A) index, where the measurement results fall within the threshold (Z-Score) of -2 SD to -3 SD (short/stunted) and -3 SD (very short/severely stunted). In 2023, 27.3% of the toddlers in Penfui Timur Village were still stunted. The purpose of this study is to ascertain how stunting reduction policies are being implemented in Penfui Timur Village, Kupang Regency. This research used a qualitative descriptive method with data collection techniques of in-depth interviews, observation and documentation. The informants in this study is 8 informants, consisting of 2 main informants and 6 supporting informants. The main informants are the head of the Penfui Timur village and the nutrition staff of the Tarus Health Center. The supporting informants are 2 posyandu cadres, mothers of stunted toddlers, pregnant women, village residents, and teenage girls.The data analysis process in this research begins by collecting data from interviews and then reducing the resulting data. After that, the data is presented and concluded. The study's result showed that although the policy has been applied effectively, it still falls short of the implementation theory's requirements. The implementers' low educational and human resource levels, the ignorance of expectant mothers and parents of children with stunted growth, and the lack of facilities and infrastructure are the contributing reasons. Although the village government's communication component with other implementing parties has been functioning smoothly, communication with the leaders of the target community has not been at its best. The policy implementers are already familiar with the methods and duties associated with their respective areas of responsibility. The bureaucratic structure's policy implementers are already familiar with the technical facets of reducing stunting. Based on the results of the study, it is recommended to increasing the knowledge involved in implementation policy for stunting reduction